High-Frequency Multiport Vector Network Analysis Methodology Using Port Extension Across Multiple VNAs - Löffler, Jens; Koch, Manuel; Breun, Sascha; Weigel, Robert (2024 54th European Microwave Conference (EuMC), 2024)
This paper presents a novel methodology that enables 8-port vector network analysis measurements with high magnitude and phase accuracy using two individual commercially available network analyzers. A maximum phase error of 0.2 degrees and a magnitude error below 0.4 up to 40 GHz is demonstrated, with a multi-port setup using two Keysight PNA-X VNAs in comparison to a standard 4-port setup. The paper shows the required hardware interconnects, as well as the proposed software and calibration algorithms. The achieved accuracy and dynamic range prove to be suitable for the 8-port characterization of crosstalk in highly dense signal routing environments, such as Tbit/s chip-to-chip interfaces, up to a higher frequency range than commercially available.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Crosstalk; Multiport; S-Parameter; SOLT; VNA